Russia 2025 scenarios for the Russian future - Lipman, Maria; Petrov, Nikolay; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Russia 2025 offers a compelling insight into Russia's future by exploring thematic scenarios ranging from politics to demographics. The widening rift between a modernizing, post-Communist society and a paternalistic government will ultimately shape developments in the coming years and will impact on state-society and Center-periphery relations.
Keywords: Political science; Public policy; Russia -- Politics and government; Economic policy; Social policy; Sociology; Political Science and International Relations; Public Policy; Sociology, general; Social Policy; Russian and Post-Soviet Politics; Economic Policy; Political Science